2002
DOI: 10.5194/hess-6-655-2002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model data fusion for river flow forecasting: an evaluation of six alternative methods based on two contrasting catchments

Abstract: This paper evaluates six published data fusion strategies for hydrological forecasting based on two contrasting catchments: the River Ouse and the Upper River Wye. The input level and discharge estimates for each river comprised a mixed set of single model forecasts. Data fusion was performed using: arithmetic-averaging, a probabilistic method in which the best model from the last time step is used to generate the current forecast, two different neural network operations and two different soft computing method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 36 publications
1
77
1
Order By: Relevance
“…This was achieved in both cases regardless of the number of merged members. This statement is consistent with Abrahart and See (2002) who showed that the most efficient data-fusion methods depended on the particular application case. However, as Georgakakos et al (2004) demonstrated, the simple mean of five model predictions consistently outperformed the best single model prediction in several catchments, it was only true at Sävja in our study.…”
Section: Discussionsupporting
confidence: 79%
“…This was achieved in both cases regardless of the number of merged members. This statement is consistent with Abrahart and See (2002) who showed that the most efficient data-fusion methods depended on the particular application case. However, as Georgakakos et al (2004) demonstrated, the simple mean of five model predictions consistently outperformed the best single model prediction in several catchments, it was only true at Sävja in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Since then there have been several more studies which have dealt with multi-model combination of hydrological models (e.g. (Abrahart and See 2002, Ajami, et al 2006, Coulibaly, et al 2005, Hsu, et al 2009, See and Openshaw 2000, Shamseldin, et al 2007, Viney, et al 2009, Xiong, et al 2001). As the nature of the combination function is unknown and no theory exists to analytically derive the combination function from a hydrological or physical point of view, previous studies have used empirical data-driven modeling to derive the combination function and such use is very appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…See and Abrahart [2001] used ANN data fusion strategies for continuous river level forecasting where data fusion is the amalgamation of information from multiple sensors and/or different data sources. Abrahart and See [2002] evaluated six data fusion strategies and found that ANN data fusion provided the best solution for a stable region. Cannon and Whitfield [2002] used a bootstrap aggregated ANN ensemble as a downscaling model to predict streamflow and changes in streamflow conditions in British Columbia, Canada.…”
Section: Introductionmentioning
confidence: 99%